Skeletal adaptations associated with pre-pubertal gymnastics participation as determined by DXA and pQCT: A systematic review and meta-analysis - Burt, L. A.; Greene, D. A.; Ducher, G.; Naughton, G. A. (Journal of Science and Medicine in Sport, 2013)
Participation in gymnastics prior to puberty offers an intriguing and unique model, particularly in girls. The individuality comes from both upper and lower limbs being exposed to high mechanical loading through year long intensive training programs, initiated at a young age. Studying this unique model and the associated changes in musculoskeletal health during growth is an area of specific interest. Previous reviews on gymnastics participation and bone health have been broad; and not limited to a particular maturation period, such as pre-puberty. Objectives: To determine the difference in skeletal health between pre-pubertal girls participating in gymnastics compared with non-gymnasts. Design: Meta-analysis. Methods: Following a systematic search, 17 studies were included in this meta-analysis. All studies used dual-energy X-ray absorptiometry to assess bone mineral density and bone mineral content. In addition, two studies included peripheral quantitative computed tomography. Results: Following the implementation of a random effects model, gymnasts were found to have greater bone properties than non-gymnasts. The largest difference in bone health between gymnasts and non-gymnasts was observed in peripheral quantitative computed tomography-derived volumetric bone mineral density at the distal radius (d = 1.06). Conclusions: Participation in gymnastics during pre-pubertal growth was associated with skeletal health benefits, particularly to the upper body.